Frasa Bahasa Wate: Phrase of Wate Language - Maturbongs, Antonius (Kibas Cenderawasih, 2023)
Various meaning and definition phrase have been made by various writer, but is not quit of congeniality phrase as a group word. In consequence, phrase basically [is] word group. If/When seen from facet forming [of] phrase, can be said that [by] phrase [is] word [relation/link] with word and word with suprasegmental elements and also situation that [do] not exceed subjek function boundary and predikat in clause. Thereby, phrase to represent word corps ( word with word, word with suprasegmental elements and situation) representing part of which not yet complete in a[n broader tuturan namely discourse and sentence (Fautngil,1997:5). Phrase only filling one function in clause. To strengthen clarification above cited one congeniality [of] phrase supporting [it] made by Elson Pickket and ( 1976: 73), namely " Phrase composed unit a in A, potentially, words more or two or, typically which but, always note but, level clouse a of slot fills." Implicit here congeniality that frase only have potency [to] consist of two word or more and clearly [do] not exceed clause characteristic namely only one function except predikat [relation/link] and object in consequence phrase to represent gatra filler in clause. This congeniality [is] weared as basis for identify phrase in this research analysi.  Starting from theory weared in this research namely analyse tagmemik, hence discussion hereinafter will be divided into function analysis, category, and role of[is each phrase interior.